Assessment of lower incisor alveolar bone width using cone-beam computed tomography images in skeletal Class III adults of different vertical patterns - Lee, Sanghee (Korean J Orthod, 2018)
OBJECTIVE: This study was performed to investigate the alveolar bone of lower incisors in skeletal Class III adults of different vertical facial patterns and to compare it with that of Class I adults using cone-beam computed tomography (CBCT) images. METHODS: CBCT images of 90 skeletal Class III and 29 Class I patients were evaluated. Class III subjects were divided by mandibular plane angle: high (SN-MP > 38.0°), normal (30.0° < SN-MP < 37.0°), and low (SN-MP < 28.0°) groups. Buccolingual alveolar bone thickness was measured using CBCT images of mandibular incisors at alveolar crest and 3, 6, and 9 mm apical levels. Linear mixed model, Bonferroni post-hoc test, and Pearson correlation analysis were used for statistical significance. RESULTS: Buccolingual alveolar bone in Class III high, normal and low angle subjects was not significantly different at alveolar crest and 3 mm apical level while lingual bone was thicker at 6 and 9 mm apical levels than on buccal side. Class III high angle group had thinner alveolar bone at all levels except at buccal alveolar crest and 9 mm apical level on lingual side compared to the Class I group. Class III high angle group showed thinner alveolar bone than the Class III normal or low angle groups in most regions. Mandibular plane angle showed negative correlations with mandibular anterior alveolar bone thickness. CONCLUSIONS: Skeletal Class III subjects with high mandibular plane angles showed thinner mandibular alveolar bone in most areas compared to normal or low angle subjects. Mandibular plane angle was negatively correlated with buccolingual alveolar bone thickness.